A Robotics Club as a Strategy to Integrate Teaching, Research, and Community Engagement: Early Results - Silva, Igor Victor Rodrigues; Silva, Lorena Nunes; Silva, Eduardo Lemes; Souza, Diogo Sampaio César; Júnio, Carlos Dias da Silva; Soares, Lívia De Maria C. M.; Freitas, Elias J. R. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2025: Anais do XVII Simpósio Brasileiro de Robótica e XVI Workshop de Robótica na Educação, 2025)
This paper presents the experience of the Robotics Club EPIIBOTS at the Federal Institute of Minas Gerais - Campus Ibirité, focusing on its integration of teaching, research, and community engagement in 2024 and 2025. Through practical activities with LEGO EV3 and Arduino, the club promotes technical training and student leadership. Its research efforts include participation in academic events and publications, while extension actions target digital inclusion through workshops for socially vulnerable youth. Using a qualitative case study approach, the work analyzes how such initiatives contribute to technical education, scientific engagement, and social impact in public vocational institutions.